Cytomegalovirus reactivation triggers the late onset of hyperthyroidism after autologous peripheral blood transplantation. (2019) - Oka, Satoko; Ono, Kazuo; Nohgawa, Masaharu
Abstract: Thyroid dysfunction is an important issue in patients receiving autologous and allogenic hematopoietic stem cell transplantation (HSCT). However, the exact mechanisms underlying thyrotoxicosis secondary to HSCT remain unclear. The present case exhibited a reversed imbalance in helper/suppressor T-cell populations and B-cell dysregulation for a long time after transplantation, and the reactivation of cytomegalovirus may have been associated with the development of clinical hyperthyroidism. The long-term monitoring of thyroid function, T-cell populations, and cytomegalovirus after HSCT is important.